Emplacement of the Fogo Island Batholith, Newfoundland - Currie, K.L. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2003)
ABSTRACT The Siluro-Devonian Fogo Island Batholith is a high-level, bimodal, sill-like unit about 7 km thick, intruded by a slightly younger, heterogeneous maﬁc unit. Stratigraphic evidence suggests emplacement of the batholith by raising of the roof without strong deformation of the host rocks. Large composite gabbro-microgranite dykes below the sill, intruded along axial planar cleavage, probably served as feeders. The upper 3– 4 km of the sill comprise homogeneous to slightly zoned, coarse, hastingsite-biotite granite. Ignimbrite sheets of similar composition above the sill suggest that the granite was emplaced beneath cover rocks no more than 1 km thick. The lower 3 km of the sill consist of heterogeneous, locally layered, maﬁc rocks. Metre-scale, non-intrusive sheets of contrasting composition mark the contact between the granitic upper and maﬁc lower part of the sill. A late inﬂux of maﬁc magma disrupted older maﬁc rocks and hybridised with granite, producing complex, heterogeneous "diorite". The local presence of A-type compositions in the granitic portion of the batholith may reﬂect diffusion during this process. A model for emplacement of the batholith assumes crustal anatexis above mantle-derived, underplated maﬁc magma, followed by passive emplacement of composite magma along tensional fractures related to movements on the Dog Bay Line, a dextral terrane boundary. Later movements on this feature controlled emplacement of further batches of magma, and ﬁnally tipped the batholith about 25° to the north, producing its present conﬁguration.